The Analysis of Maxim in Student and Lecturer Conversations through WhatsApp Messenger - Indriyanto Indriyanto (Journal of English Language and Education, 2023)
The presence of instant messaging applications and its practice in daily life makes it easier for us to communicate without space and time limitations. This study aims to describe the adherence to politeness principles in WhatsApp messages sent by students to lecturers during thesis guidance. The method used is the descriptive method. The collecting data is in the form of utterances in WhatsApp messages which show adherence to the principle of linguistic politeness. The data collection technique used is the documentation. Data analysis steps (1) collecting WhatsApp messages, (2) reading messages, (3) identifying maxims, (4) classifying maxims, (5) analysing maxims, and (6) conclusions. The results of the study show that speech between speakers and speech partners (lecturers and students) fulfils the rules/principles of maxims.